Self esteem and self agency in first episode psychosis: Ethnic variation and relationship with clinical presentation. Issue 2 (30th June 2015) - Ciufolini, Simone; Morgan, Craig; Morgan, Kevin; Fearon, Paul; Boydell, Jane; Hutchinson, Gerard; Demjaha, Arsjme; Girardi, Paolo; Doody, Gill A.; Jones, Peter B.; Murray, Robin; Dazzan, Paola
Abstract: The impact of self esteem and Locus of Control (LoC) on clinical presentation across different ethnic groups of patients at their first psychotic episode (FEP) remains unknown. We explored these constructs in 257 FEP patients (Black n =95; White British n =119) and 341 controls (Black n =70; White British n =226), and examined their relationship with symptom dimensions and pathways to care. FEP patients presented lower self-esteem and a more external LoC than controls. Lower self esteem was associated with a specific symptoms profile (more manic and less negative symptoms), and with factors predictive of poorer outcome (longer duration of untreated psychosis (DUP) and compulsory mode of admission). A more external LoC was associated with more negative symptoms and an insidious onset. When we explored these constructs across different ethnic groups, we found that Black patients had significantly higher self esteem than White British. This was again associated with specific symptom profiles. While British patients with lower self esteem were more likely to report delusions, hallucinations and negative symptoms, Black patients with a lower self esteem showed less disorganization symptoms. These findings suggest that self esteem and LoC may represent one way in which social experiences and contexts differentially influence vulnerable individuals along the pathway to psychosis. Highlights: First study to explore self-esteem and self-agency and symptom dimensions in FEP. Higher self-esteem associated with more manic symptoms shorter DUP and compulsory admission. Reduced sense of self-agency associated with less negative symptoms and insidious onset. Lower self-esteem associated increased reality distortion and negative symptoms in White British patients. Lower self-esteem correlated with less symptoms of disorganization in Black patients.